Effectiveness of using the Mask with Innovative Nutrition Adaptor of Non-Invasive Mechanical Ventilation Machine for Patients with COVID-19 - Omar Thamer Hachim, Musaab Majid Abdulwahhab (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Oral feeding of COVID-19 patients receiving NIMV is not possible due to the drastic demand for oxygenation. Removal of the mask for feeding is not possible.The presence of the innovative nutritional adaptor in the non-invasive ventilation mask(NA-NIMV) enables eating mixed foods and liquids through the mouth without the need to remove the mask, contrary to what happens in the standard hospital mask(SH-NIMV) where the mask is removed for feeding or using parenteral nutrition, and the use of the NA-NIMV does not cause air leakage during its use and thus maintains the level of oxygen saturation, respiratory rate, and heart rate. The objective of this study was designed to determine the effect of the mask with the innovative nutritional adaptor of NIVM (NA-NIMV) on the nutritional status of patients with COVID-19 in the ICU concerning air leakage, oxygen saturation (SPO2), respiratory rate (RR), and pulse rate (PR). Design: A crossover randomised controlled trial (RCT ) design was used to accomplish the aforementioned goals. Methods: A randomised sample of 24 patients with Covid-19 who were hospitalized in the ICU in two public hospitals, in Baghdad city. we include adult patients infected with COVID-19 who required NIV with (SH-NIMV) and (NA-NIMV), the intervention was: every patient received two interventions, apply (SH-NIMV) for 24hrs and received (NA-NIVM )for 24hrs. The outcomes of the endeavour were the amount of nutrition provided Calculated according to ESPEN guidelines, air leakage, SPO2, RR, and PR during each intervention. Results: A significant statistical difference between calories provided during apply (SH-NIMV) (Average Required calories= 1917, Mean Difference=1644.417* , Average Provided=272 = 14% from total calories need) and NA-NIVM(Average Required calories= 1917, Mean Difference=110.583* Average Provided=1806 = 94% from total calories need), a proteins (SH-NIMV) (Average Required proteins = 82.82917g Mean Difference=66.075*g , Average Provided=17g = 20% from total proteins need) and NA-NIVM(Average Required proteins = 66.075*g, Mean Difference=4.188*, Average Provided=79 = 95% from total proteins need), the mean differences between SH-NIMV and NA-NIMV in SPO2 Sig. (2-tailed = .0001), RR Sig. (2-tailed = .0001), air leakage Sig. (2-tailed = .0001), RR Sig. (2-tailed = .0001), PR Sig. (2-tailed = .001).Conclusion: Large amounts of calories and proteins while maintaining the absence of air leakage, SPO2, RR, and PR when using the NA-NIMV contrarily when using the SH-NIMV. Recommendation: manufacture a mask with a nutritional adaptor (NA-NIMV) according to the researchers’ design. Recourse to the NA-NIMV in the ICU for patients undergoing NIMV. Trail Registration: Clinical Trial Registry https://www.irct.ir/ reference number (IRCT20211022052840N1).